The Effect of Ethrel Solution Concentration on the Degreening Process of Orange (Citrus reticulata) - Muharraran, Nazha Duta Ulkitasalka; Raharjo, Dwi; Priyono, Suko (FoodTech: Jurnal Teknologi Pangan, 2025)
Oranges are among the most widely cultivated fruits in Indonesia. Generally, the skin color of oranges at harvest is still greenish. Most consumers prefer oranges with orange-colored skin as the color indicates full ripeness and a sweet taste. The green color on orange skin can be improved through postharvest treatment known as degreening, using an ethrel solution. The study goal is to determine the optimal concentration of ethrel solution for the degreening process of honey milk oranges. The research employed a Randomized Block Design (RBD) with one factor that is ethrel solution concentration, consisting of six treatments (0, 250, 500, 750, 1000, and 1250 ppm). Each treatment was repeated four times, resulting in 24 sample units. The observed parameters included weight loss, color, total titratable acidity, total soluble solids, vitamin C, and total chlorophyll content. The optimal ethrel solution concentration was determined by using the De Garmo effectiveness index method. The results showed that an ethrel solution concentration of 1250 ppm was the best treatment based on the effectiveness index, with the following characteristics: weight loss of 2.34%, total acidity of 0.71%, total chlorophyll of 1.97 mg/L, total soluble solids of 10.8°Brix, vitamin C content of 213.40 mg, L value of 40.79, a* value of 8.19, and b* value of 48.70.